2012
DOI: 10.1140/epjd/e2012-30499-y
|View full text |Cite
|
Sign up to set email alerts
|

EUV magnetic-dipole lines from highly-charged high-Z ions with an open 3d shell

Abstract: Abstract. The electron beam ion trap (EBIT) at the National Institute of Standards and Technology was used to produce highly-charged ions of hafnium, tantalum and gold with an open 3d shell. The extremeultraviolet (EUV) spectra from these ions were recorded with a flat-field grazing-incidence spectrometer in the wavelength range of 4.5 nm to 25 nm. A total of 133 new spectral lines, primarily due to magneticdipole transitions within the ground-state 3d n configurations of the Co-like to K-like ions, were ident… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 41 publications
6
48
0
Order By: Relevance
“…Up to now, the spectral line from the 3d 9 2 D 3/2 → 3d 9 2 D 5/2 transition has only been directly obsereved for seven of the Co-like ions(Zr 13+ , Nb 14+ , Mo 15+ , Hf 45+ , Ta 46+ , W 47+ and Au 52+ [13][14][15]).…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the spectral line from the 3d 9 2 D 3/2 → 3d 9 2 D 5/2 transition has only been directly obsereved for seven of the Co-like ions(Zr 13+ , Nb 14+ , Mo 15+ , Hf 45+ , Ta 46+ , W 47+ and Au 52+ [13][14][15]).…”
Section: Introductionmentioning
confidence: 99%
“…There exist many experimental investigations of forbidden transitions within the 3s 2 3p 6 3d k (k = 1 − 9) ground configurations in these M-shell ions with measurements from EBITs at NIST [1][2][3][12][13][14][15] and at the Lawrence Livermore National Laboratory [10]. There are also several theoretical studies (see e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%
“…While elements with a high-Z atomic number have these effects amplified, ions in the medium-Z region have special importance because they allow for more accurate experiments and provide constraints to theoretical trends. In the past few years, the electron beam ion trap (EBIT) research program at the National Institute of Standards and Technology (NIST) has reported accurate measurements in the extreme ultraviolet (EUV) region that focus on systematic observations of transitions in L-shell, M-shell and N-shell ions [2][3][4][5][6][7][8][9][10][11][12][13][14]. The work reported here extends these results to a range of previously unobserved transitions of a fifth row element, yttrium.…”
Section: Introductionmentioning
confidence: 58%